Determinants of Nutritional Status Among Pregnant Women in Flood-Prone and Non-Flood-Prone Communities in Rivers State - Emordi, Nnenna Ali; Robinson-Bassey, Grace Chinyere; Omisakin, Folorunso Dipo; Okankwu, Elizabeth Amini (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
The study investigated the determinants of nutritional status among pregnant women in flood-prone and non-flood-prone communities. It specifically examined the nutritional knowledge of pregnant women and the socio-demographic factors influencing their haemoglobin levels. Two research questions and one null hypothesis tested at a 0.05 level of significance guided the study. A descriptive cross-sectional survey design was adopted to assess the condition of pregnant women at a specific point in time. The population of the study comprised all pregnant women attending antenatal clinics in selected primary healthcare facilities, while a sample of 400 participants was targeted. Out of these, 368 duly completed and returned the questionnaire, representing a 92% response rate. A multistage sampling technique was employed to ensure fair representation of both flood-prone and non-flood-prone communities. Data were collected using a structured questionnaire titled Determinants of Nutritional Status of Pregnant Women in Flood-Prone and Non-Flood-Prone Communities Questionnaire (DNSPWFPNFPQ), which consisted of sections on nutritional knowledge and socio-demographic factors influencing nutritional status. Face and content validation were carried out by three experts, and the reliability of the instrument was established using the Cronbach Alpha method, yielding a coefficient of 0.86. The collected data were analysed using descriptive statistics such as frequency and percentage to answer the research questions, while Chi-square analysis was used to test the hypothesis at a 0.05 significance level. Findings revealed that many pregnant women had limited nutritional knowledge, particularly in flood-prone areas, which influenced their dietary decisions and health status. The results also showed that education and occupation significantly affected haemoglobin levels, while age and family size had no meaningful association. It was concluded that nutritional knowledge and socio-economic factors play an important role in determining the nutritional wellbeing of pregnant women. Based on the findings, it was recommended that health authorities should enhance nutrition education during antenatal care and promote policies that support women’s education and economic empowerment to reduce anaemia and improve maternal health outcomes.